2009
DOI: 10.2217/nnm.09.38
|View full text |Cite
|
Sign up to set email alerts
|

NanoART, NeuroAIDS and CNS Drug Delivery

Abstract: A broad range of nanomedicines is being developed to improve drug delivery for CNS disorders. The structure of the blood-brain barrier (BBB), the presence of efflux pumps and the expression of metabolic enzymes pose hurdles for drug-brain entry. Nanoformulations can circumvent the BBB to improve CNS-directed drug delivery by affecting such pumps and enzymes. Alternatively, they can be optimized to affect their size, shape, and protein and lipid coatings to facilitate drug uptake, release and ingress across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 133 publications
0
102
0
5
Order By: Relevance
“…[1][2][3][4][5] However, the short half-life of the drugs necessitates multiple daily dosing schedules limiting both access and compliance. Moreover, failure of ART penetration into sanctuaries of persistent viral replication including the lymphoreticular and central nervous systems, and a range of secondary drug-induced toxicities further highlight the limitations of chronic drug treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, the short half-life of the drugs necessitates multiple daily dosing schedules limiting both access and compliance. Moreover, failure of ART penetration into sanctuaries of persistent viral replication including the lymphoreticular and central nervous systems, and a range of secondary drug-induced toxicities further highlight the limitations of chronic drug treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of nanocarriers includes its ability to bypass the multidrug-resistant transporters, which may efflux drugs entering freely through the plasma membrane. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Inorganic solid lipid nanoparticles liposomes, polymeric micelles, dendrimers, cyclodextrins, and cell-based nanoformulations have been studied for delivery of drugs intended for HIV prevention or therapy. 43 For anti-HIV drugs to be effective, adequate distribution to specific sites in the body must be achieved, and effective drug concentrations must be maintained at those sites for the required period of time.…”
Section: Targeted Drug Delivery Of Antiretroviralsmentioning
confidence: 99%
“…24,29 Nowacek and Gendelman have shown that a single intravenous dose of the nano-ART can elicit high-sustained tissue and plasma drug levels of antiretroviral drugs in the reticuloendothelial system and brain. 26 Nano-ART can be taken up within minutes by circulating monocytes and released in tissues over a period of 2 weeks. [56][57][58][59][60] Theoretically, cell-based nano-ART would travel to sites of inflammation and release drug(s) slowly with limited tissue toxicities.…”
Section: Targeted Drug Delivery Of Antiretroviralsmentioning
confidence: 99%
See 2 more Smart Citations